(untitled) (Altre Modernità, 2019)
Within the context of studies on cinema and memory of the dictatorship in Argentina, my article deals with the work of those authors who experienced state terrorism during their childhood and considers the case of the film Infancia clandestina (2011), directed and co-written by the filmmaker Benjamín Ávil. The main interest lies in the way the film constructs the figures of the parents of the protagonist, the relationship between them, and finally, his own subjectivity. My analysis will examine the film as an attempt to dig into the contradictory feelings of the protagonist, caught between the wishes of his age, the conditions of the armed struggle and State Terrorism. Furthermore, I attempt to consider the procedures and narrative resources that show the evolution and critical points of the protagonist feelings, with particular attention to the animations of the painter and graphic artist Andy Riva, as well as the presence of dreams and memory objects, such as recordings and photographs.